Advances in pathogenesis and nanoparticles (NPs)-mediated treatment of psoriasis - Shen, Qian; Liu, Rong; Tan, Shiyu; Xu, Xiaoding; Fang, Junyue; Li, Rong (Frontiers in Immunology, 2022)
Psoriasis is a chronic autoimmune inflammatory skin disease that affects around 2%~3% of the global population and imposes a heavy physical and psychological distress on patients. In the past few decades, with the rapid development of molecular biology and cell biology, the inherent pathogenesis of psoriasis has been gradually elucidated, in which cytokine inflammatory loops, cell signaling pathways, and epigenetic factors such as miRNAs have been demonstrated to play important roles in regulating the development and progression of psoriasis. More importantly, understanding the pathogenesis of psoriasis has promoted the development of effective treatment for psoriasis. In this review, we systemically summarized the molecular mechanisms regulating the development and progression psoriasis, introduced various therapeutics used for clinical psoriasis therapy, and highlighted the recent advances in nanoparticles (NPs)-mediated drug delivery for psoriasis treatment.